Identifikasi Penderita Hipertensi untuk Melakukan Pengobatan secara Teratur Melalui KonselingATMENTREGULARLY THROUGH COUNSELING IN THE BADIT AREA OF GADO-GADO PADANG - Sri Siswati (invotek, 2020)
Abstract— Disease is an uncertainty or something that is uncertain when it comes, therefore public health services Non-Communicable Diseases (PTMs need to be prevented. This study presents descriptive PTMs examined in the Bukit Gado-Gado Gunung Padang area. Research aimed at 1) presents PTM risk factors public health who will exercise early in the morning at Bukit Gado-Gado. 2) to measure the risk factors experienced by the community in PTM 3) Providing public health counseling The research procedure was carried out by looking at a picture of community health risk factors, analyzing the achievement of healthy families from several sources and providing solutions to the community by using digital equipment regularly .. The results show the highest risk factor for hypertension is 60%. Counseling to the community to always carry out health checks, get rid of cigarette smoke, diligent physical activity, balanced diet, adequate rest and control of stress. Analysis shows that the family approach can prevent risk factors for Non-Communicable Diseas(NCD), because it is closest to the community. Therefore, it can be concluded that the family approach model wherever located can prevent risk factors for NCD.. Key word : Non-Communicable Diseases, Counseling, Family Approach